Leveraging Ways to Decarbonise the Supply Chain Processes in the Oil and Gas Industry for a Sustainable Green Environment - Bhat, Venugopal (Digital Repository of Theses, 2026)
In the contemporary era, the terms Decarbonization, Carbon Footprint, Net Zero Emission, and Sustainability have transcended their status as mere buzzwords. They have become pivotal concepts that are integral to the establishment of a green environment for future generations. The importance these issues is emphasized by the changing weather impacts and the rising recognition of the environmental impressions of industrial activities. Today, supply chain business processes and solutions are increasingly automated and standardized on a global scale to achieve efficiency. However, this drive for efficiency often overlooks a critical question: Are all organizations across various industries actively working to decrease emissions from the supply chains? The unfortunate reality is that many are not. This gap highlights the need for a concerted effort to identify the unique roles that suppliers, logistics partners, and other key players can play in decarbonizing the value chain. Furthermore, there is a pressing need for industry-wide commitment to reducing carbon footprints, as well as careful estimation of the environmental impacts. The key objective of this research is to provide a complete analyse the recent works and industry practices related to decarbonization initiatives. By doing so, the study aims to outline a hypothetical context for defining a methodology to measure carbon emissions across the supply chain and logistics portfolio. This framework will offer a holistic understanding of the past, present, and future directions of decarbonization and its contributions. The dissertation will delve into how governments can scale up the adoption of technologies involved in the decarbonization of supply chains, particularly within the energy sector. This exploration will be based on a combination of descriptive and analytical research methodologies, utilizing surveys from reliable databases such as ScienceDirect, Scopus, ResearchGate, and Google Scholar. One of the key aspects of this study is the classification of emissions according to the Greenhouse Gas (GHG) Practise. The practise classifies emissions into three scopes: Scope 1 (Direct Emissions), Scope 2 (Indirect Emissions from energy consumption), and Scope 3 (Other Indirect Emissions) (GHG Protocol, 2023; IEA, 2024; World Economic Forum, 2023). By breaking down the problem statement into these categories, the research aims to provide a focused analysis of resilient and sustainable solution outcomes. These solutions are not only applicable to the oil and gas (energy) industries but also to other organizations striving to reduce their carbon footprints, particularly, those arising by Scope 3 emissions. The research will also explore the potential development of a digital product designed to track carbon emissions across various categories. These categories include Green Purchasing (GP) and Sustainable Sourcing, Green Logistics and Packaging, and collaborative carbon tracking with partners. Such a product could be a valuable tool for administrations looking for to boost their ecological accountability and transparency. In summary, this dissertation seeks to bridge the gap between the theoretical understanding of decarbonization and its practical application within the supply chain(GHG Protocol, 2023; World Economic Forum, 2023; IEA, 2024). By critically reviewing prevailing industry practices and developing a structured framework for the measurement and management of carbon emissions, this study seeks to support the wider objective of strengthening supply-chain sustainability and resilience (GHG Protocol, 2023; World Economic Forum, 2023; CDP, 2024). The outcomes of this study are intended to guide organizations in adopting scalable and impactful decarbonisation strategies that contribute to long-term environmental sustainability (Sindhwani et al., 2023).